High-pid-resistant packaging adhesive film and preparation method thereof

CN117625053BActive Publication Date: 2026-10-27WANHUA CHEM GRP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202210979023.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-16
Publication Date
2026-10-27
Estimated Expiration
2042-08-16

AI Technical Summary

Technical Problem

但是,上述两种方法都有缺点:POE胶膜的价格较高、交联速度慢,所需层压时间长;添加离子捕捉助剂会影响胶膜光学性能,导致雾度上升

Benefits of technology

[0024]本发明采用聚醚嵌段酰胺共聚物PEBA作为抗PID助剂,其脂肪族聚酰胺链段作为硬段,聚醚链段为柔性软段,二者相互协同,综合提升组件的抗PID性能。其中,聚醚软段通过亲水性基团的吸湿作用、“芯壳结构”的导电性表层分布,构成泄漏电荷的通道,从而达到封装胶膜抗PID的目的;而脂肪族长碳链硬段增加了PEBA与POE的相容性,使得助剂在基体树脂中分散均匀,有利于湿漏电流的耗散,二者共同发挥作用,从而使得组件具有优异的抗PID性能,使得光伏组件具备长期稳定运行的能力。该聚醚嵌段酰胺共聚物通过少量添加,便可显著提升光伏组件的抗PID性能,所制得的胶膜适配双面PREC组件的封装,经过-1500V/96h PID测试后组件正面功率衰减在1%以内。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003799589060000111
    Figure BDA0003799589060000111
  • Figure BDA0003799589060000121
    Figure BDA0003799589060000121
  • Figure BDA0003799589060000131
    Figure BDA0003799589060000131
Patent Text Reader

Abstract

The application relates to a high-PID-resistant packaging adhesive film and a preparation method thereof. The high-PID-resistant packaging adhesive film comprises 85-100 parts by weight of a base resin, 0.01-0.5 parts by weight of an anti-aging additive, 0.05-1 parts by weight of a coupling agent, 0.1-1 parts by weight of a crosslinking agent and 1-5 parts by weight of an anti-PID additive. The high-PID-resistant packaging adhesive film for photovoltaic modules is prepared through high-speed mixing for 2-5 hours and then being extruded into a film. The photovoltaic packaging adhesive film prepared by the method can solve the problem of PID power attenuation of the module, and has more excellent optical performance and higher power generation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical fields:

[0001] This invention relates to an encapsulating film, and more particularly to a high PID-resistant encapsulating film and its preparation method. Background technology:

[0002] As one of the most competitive new energy sources, photovoltaic power generation is expected to continue its rapid expansion in the future. While the corresponding encapsulating film material EVA / POE accounts for only about 7% of the total cost of photovoltaic modules, it is a crucial factor determining the quality and lifespan of these modules. Once the encapsulating film and backsheet of the battery module begin to yellow or crack, the batteries are prone to premature failure. Long-term operation of photovoltaic modules in high-voltage environments can easily lead to leakage current channels between the encapsulation material, backsheet, glass, and frame. A large amount of charge accumulates on the surface of the battery cells, causing significant passivation and resulting in a substantial degradation in module performance—a phenomenon known as PID (Potential Inertial Discharge) phenomenon.

[0003] EVA is relatively inexpensive, easy to process, durable, has a fast cross-linking speed, and good adhesion to glass and backsheets. However, VA is prone to hydrolysis under light, oxygen, and humid heat environments, producing acetic acid, which corrodes the cell surface and solder ribbons. It also reacts with sodium in the glass, generating a large number of freely moving sodium ions, causing power degradation. Furthermore, EVA is prone to yellowing under light and heat environments, affecting light transmittance and causing overall module power loss. POE has good material properties, including high volume resistivity, high water vapor barrier properties, low-temperature resistance, and resistance to yellowing. However, POE has low polarity, and polar additives and solvents easily precipitate onto the film surface during encapsulation, resulting in a smooth surface prone to displacement. It also has a higher processing difficulty, and the film lip is prone to material buildup. Regardless of whether it's EVA or POE, as photovoltaic encapsulation materials, it's still difficult to avoid the PID (Power Degradation) problem in module power during actual use.

[0004] The main factors influencing PID attenuation are: ① Na+ ion migration; ② EVA molecular chain hydrolysis. Currently, the mainstream methods for achieving anti-PID films are: ① using high-volume-resistance polyolefin elastomer (POE) instead of EVA; ② adding additives with sodium ion-scavenging capabilities to the formulation. However, both methods have drawbacks: POE films are expensive, have slow cross-linking speeds, and require long lamination times; adding ion-scavenging additives can affect the film's optical properties, leading to increased haze. Existing PID additives, based on their mechanisms of action, are mainly ethoxylated or propoxylated acrylates, organic / inorganic ion scavengers, etc. Among them, patent CN112898920A achieves anti-PID effect by adding pyrophosphate and / or metal oxides as ion exchangers; patent CN113234402A achieves anti-PID effect by adding zirconium phosphate and diisopropyl xanthate disulfide as ion scavengers; however, the addition of inorganic and small molecule additives is always accompanied by the problem of additive precipitation, thus affecting the long-term performance of the encapsulating film. Patent CN113122164A adds the anti-hydrolysis additive polycarbodiimide and the acid absorbent magnesium hydroxide to the film, achieving anti-PID effect by weakening the hydrolysis of EVA molecular chains; however, this method is not suitable for POE films, so the effect is limited. Patent CN109337599A adds polyether ester amide as a charge dissipator to the film; however, polyether ester amide contains hard segments of semi-aromatic polyamide, and the presence of aromatic rings in its structure makes it incompatible with resins such as POE, and the additive is prone to precipitation, resulting in a decrease in the performance of the film. Furthermore, the introduction of aromatic ring structures makes the encapsulant film susceptible to yellowing, thus significantly reducing the performance of photovoltaic modules in actual use.

[0005] The development of a highly PID-resistant encapsulating film with significant anti-PID effects, excellent optical performance, and good power generation, as well as its preparation method, is of great significance. Summary of the Invention:

[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0007] This invention provides a high PID-resistant encapsulating film, comprising the following raw materials in parts by weight:

[0008] 85-100 parts of base resin,

[0009] Anti-aging additive 0.01-0.5 parts,

[0010] Coupling agent 0.05-1 part,

[0011] Crosslinking agent 0.1 to 1 part,

[0012] 1-5 parts of anti-PID additive.

[0013] Preferably, the base resin is one or both of POE resin and EVA resin. The EVA resin preferably has a melt index of 15–30 g / 10 min and a VA content of 28–33%; the POE resin preferably has a melt index of 2–50 g / 10 min.

[0014] Preferably, the anti-aging additive includes one or more of ultraviolet light absorbers and light stabilizers. The ultraviolet light absorber is selected from one or more of 2,4-dihydroxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, 2-(2'-hydroxy-5'-octylphenyl)-benzotriazole, 2-[2,4-bis(2,4-xylyl)-2-(1,3,5-triazinyl)5-octyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-hexyloxyphenol, bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, or 2,2,6,6-tetramethyl-4-piperidinyl stearate. The light stabilizer is selected from one or more of 2-(2H-benzotriazol-2-yl)-6-dodecyl-4-methylphenol, bis(2,2,6,6,-tetramethyl-4-piperidinyl) sebacate or polysuccinate (4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol).

[0015] Preferably, the coupling agent is a silane coupling agent selected from one or more of methacryloyloxypropyltrimethoxysilane, 3-methacryloyloxypropylmethyldimethoxysilane, vinyltriethoxysilane, vinyltriperoxytert-butylsilane, γ-methacryloyloxypropyltrimethoxysilane, vinyltriacetoxysilane, 3-glycidylpropyltrimethoxysilane, 3-aminopropyltriethoxysilane, or vinylalkoxysilane oligomers.

[0016] Preferably, the crosslinking agent is selected from one or more of the following: di(4-methylbenzoyl)peroxide, cumene peroxide, di-tert-butyl peroxide, dicumene hydrogen peroxide, 2,5-dimethyl-2,5-di-tert-butyl peroxide, tert-butyl peroxyhexyl carbonate, benzoyl peroxide, cyclohexanone peroxide, tert-butyl peroxybenzoate, tert-butyl peracetate, tert-butyl peroxide-3,5,5-trimethylhexanoate, trimethylolpropane trimethacrylate, 2-trimethylolpropane tetraacrylate, pentaerythritol triacrylate, propoxylated neopentyl glycol diacrylate, diethylene glycol dimethacrylate, or ethoxylated trimethylolpropane triacrylate.

[0017] Preferably, the anti-PID additive is a polyether block amide copolymer (PEBA) containing aliphatic polyamide segments and polyether segments, which can be prepared using the method described in patent CN101426834A. The weight percentage of the polyether segments is 35-65%, and the weight percentage of the aliphatic polyamide segments is 35-65%.

[0018] Preferably, the polyether soft segment is a polyethylene glycol segment, a polypropylene glycol segment, or a polybutylene glycol segment.

[0019] Preferably, the aliphatic polyamide segment is a polyamide segment prepared by reacting an aliphatic diamine with an aliphatic diacid. The aliphatic diamine can be a C6-C20 alkyl diamine, and the aliphatic diacid can be a C6-C20 alkyl diacid, etc.

[0020] Preferably, the number average molecular weight of the polyether segments is 500-4500 g / mol, and the number average molecular weight of the aliphatic polyamide segments is 500-3000 g / mol.

[0021] A method for preparing a high PID-resistant encapsulating film involves mixing a base resin, an anti-aging agent, a coupling agent, a crosslinking agent, and an anti-PID agent evenly, stirring, and after the agent is fully absorbed, casting and extruding the mixture at a temperature of 70–120°C to obtain a high PID-resistant encapsulating film for photovoltaic modules.

[0022] Preferably, the processing method is casting or calendering.

[0023] Preferably, the above raw materials need to be mixed and stirred at high speed for 2-5 hours, with the preferred speed being 90-300 rpm.

[0024] This invention uses polyether block amide copolymer (PEBA) as an anti-PID additive. The aliphatic polyamide segments act as hard segments, while the polyether segments are flexible soft segments. These two components work synergistically to comprehensively improve the anti-PID performance of the module. Specifically, the polyether soft segments, through the hygroscopic effect of their hydrophilic groups and the conductive surface distribution of the "core-shell structure," form channels for leakage charge, thereby achieving the anti-PID purpose of the encapsulation film. Meanwhile, the aliphatic long carbon chain hard segments increase the compatibility of PEBA with POE, ensuring uniform dispersion of the additive in the matrix resin and facilitating the dissipation of wet leakage current. The combined effect of these two components results in excellent anti-PID performance for the module, enabling long-term stable operation of the photovoltaic module. This polyether block amide copolymer, with only a small amount added, can significantly improve the anti-PID performance of photovoltaic modules. The resulting encapsulation film is suitable for encapsulating bifacial PREC modules, and after a -1500V / 96h PID test, the front-side power decay of the module is less than 1%. Detailed Implementation

[0025] The following embodiments illustrate the present invention; however, they do not limit its scope.

[0026] Raw material source:

[0027] The polyether block amide copolymers and polyether ester amides used in the following examples and comparative examples can be prepared using the method described in patent CN101426834 A. Unless otherwise specified, the raw materials used in the examples and comparative examples of this invention can be purchased commercially.

[0028] Polyether block amide copolymer 1: Prepared from polyamide 6.18 blocks with a hard segment molar mass of 2000 g / mol and polypropylene glycol (PPG) blocks with a soft segment molar mass of 1500 g / mol. Specifically: 2.32 kg of hexamethylenediamine and 6.3 kg of octadecanoic acid were added to an autoclave equipped with a stirrer to obtain polyamide 6.18 blocks. The resulting mixture was then placed under an inert atmosphere and heated until the temperature reached 250 °C and the pressure reached 32 bar. After holding for 1 hour, a depressurization operation was performed for another hour to return to atmospheric pressure.

[0029] Subsequently, 5.74 kg of polypropylene glycol (PPG) with a molar mass of 1500 g / mol and 15 g of tetrabutyl titanate (Zr(OBu)4) catalyst were added to the reactor, and polymerization was completed at 240 °C and an absolute pressure of 8 mbar (800 Pa). In the final product, polyether block amide copolymer 1, the number-average molecular weight of the soft segment PPG was 1500 g / mol, the weight percentage of the soft segment was 40%, and the number-average molecular weight of the hard segment aliphatic polyamide 6.18 was 2000 g / mol.

[0030] Polyether block amide copolymer 2: Prepared from polyamide 10.14 blocks with a hard segment molar mass of 2000 g / mol and polybutanediol PTMG blocks with a soft segment molar mass of 3000 g / mol. Specifically: 3.44 kg of decanediamine and 5.7 kg of tetradecanoic acid were added to an autoclave equipped with a stirrer to obtain polyamide 10.14 blocks. The resulting mixture was then placed under an inert atmosphere and heated until the temperature reached 250 °C and the pressure reached 32 bar. After holding for 1 hour, a depressurization operation was performed for another hour to return to atmospheric pressure.

[0031] Subsequently, 13.71 kg of polybutanediol PTMG (3000 g / mol) and 30 g of tetrabutyl titanate Zr(OBu)4 catalyst were added to the reactor, and polymerization was completed at 240 °C and 8 mbar (800 Pa) absolute pressure. In the final product, polyether block amide copolymer 2, the number-average molecular weight of the soft segment PTMG was 3000 g / mol, the weight percentage of the soft segment was 60%, and the number-average molecular weight of the hard segment aliphatic polyamide 10.14 was 2000 g / mol.

[0032] Polyether block amide copolymer 3: Prepared from polyamide 6.14 blocks with a hard segment molar mass of 3000 g / mol and polyethylene glycol PEG blocks with a soft segment molar mass of 4500 g / mol. Specifically: 2.32 kg of 1,6-hexanediamine and 5.7 kg of tetradecanoic acid were added to an autoclave equipped with a stirrer to obtain polyamide 6.14 blocks. The resulting mixture was then placed under an inert atmosphere and heated until the temperature reached 250 °C and the pressure reached 32 bar. After holding for 1 hour, a depressurization operation was performed for another hour to return to atmospheric pressure.

[0033] Subsequently, 8 kg of polyethylene glycol (PEG) and 30 g of tetrabutyl titanate (Tb) 4500 g / mol were added to the reactor, and polymerization was completed at 240 °C and 8 mbar (800 Pa) absolute pressure. The final product, polyether block amide copolymer 3, had a soft segment PEG number-average molecular weight of 4500 g / mol, representing 50% of the soft segment by weight, and a hard segment aliphatic polyamide 6.14 with a number-average molecular weight of 3000 g / mol.

[0034] Polyether block amide copolymer 4: Prepared from polyamide 10.14 blocks with a hard segment molar mass of 2000 g / mol and polybutanediol PTMG blocks with a soft segment molar mass of 3000 g / mol. Specifically: 3.1 kg of 1,10-decanediamine and 5.13 kg of tetradecanoic acid were added to an autoclave equipped with a stirrer to obtain polyamide 10.14 blocks. The resulting mixture was then placed under an inert atmosphere and heated until the temperature reached 250 °C and the pressure reached 32 bar. After holding for 1 hour, a depressurization operation was performed for another hour to return to atmospheric pressure.

[0035] Subsequently, 47 kg of polybutanediol PTMG (3000 g / mol) and 30 g of tetrabutyl titanate Zr(OBu)4 catalyst were added to the reactor, and polymerization was completed at 240 °C and 8 mbar (800 Pa) absolute pressure. In the final product, polyether block amide copolymer 4, the number-average molecular weight of the soft segment PTMG was 3000 g / mol, the weight percentage of the soft segment was 85%, and the number-average molecular weight of the hard segment aliphatic polyamide 10.14 was 2000 g / mol.

[0036] Polyether ester amide 1: Prepared from polyamide blocks with a hard segment molar mass of 2000 g / mol and polybutanediol PTMG blocks with a soft segment molar mass of 3000 g / mol. Specifically: 2.75 kg of 1,10-decanediamine and 5.1 kg of 1,4-bis(4-carboxyphenyl)benzene were added to an autoclave equipped with a stirrer to obtain polyamide blocks. The resulting mixture was then placed under an inert atmosphere and heated until the temperature reached 250 °C and the pressure reached 32 bar. After holding for 1 hour, a depressurization operation was performed for another hour to return to atmospheric pressure.

[0037] Subsequently, 11.77 kg of polybutanediol (PTMG) and 30 g of tetrabutyl titanate (Tb) 4 catalyst (30 g) were added to the reactor, and polymerization was completed at 240 °C and 8 mbar (800 Pa) absolute pressure. The final product, polyether ester amide 1, had a soft segment PTMG number-average molecular weight of 3000 g / mol, representing 60% of the soft segment by weight, and a hard segment polyamide number-average molecular weight of 2000 g / mol.

[0038] Example 1 (Polyether block amide copolymer 1):

[0039] A highly PID-resistant encapsulating film comprises the following raw materials in parts by weight:

[0040] The mixture comprises 100 parts of ethylene-vinyl acetate copolymer (EVA) resin, 0.2 parts of anti-aging agent, 0.2 parts of coupling agent, 0.8 parts of crosslinking agent, and 2 parts of anti-PID agent. The EVA resin contains 20% vinyl acetate (VA) by mass, has a melt index of 25 g / 10 min, and the anti-aging agent includes 0.1 parts of UV absorber and 0.1 parts of light stabilizer. The UV absorber is 2-hydroxy-4-n-octyloxybenzophenone, the light stabilizer is bis(2,2,6,6,-tetramethyl-4-piperidinyl) sebacate, the coupling agent is vinyltriperoxytert-butylsilane, the crosslinking agent is tert-butyl peroxycarbonate isopropyl ester, and the anti-PID agent is polyether block amide copolymer 1.

[0041] The above-mentioned resin and additive composition was mixed in a mixer at 200 rpm for 2 hours. After mixing, it was fed into an extruder for casting, and photovoltaic encapsulation film was prepared through melt extrusion, casting film formation, cooling, slitting and winding. The extrusion temperature of the casting machine was 100℃, the screw speed was 40 rpm, the traction speed was 0.7 rpm, and the winding speed was 1.2 rpm. Subsequently, tempered glass, encapsulation film, crystalline silicon solar cell, encapsulation film and float glass were placed in the order from top to bottom, and laminated at 145℃ to obtain a double-glass photovoltaic module.

[0042] Example 2 (Polyether block amide copolymer 2):

[0043] A highly PID-resistant encapsulating film comprises the following raw materials in parts by weight:

[0044] 90 parts of POE resin, 0.04 parts of anti-aging additive, 0.02 parts of coupling agent, 0.3 parts of crosslinking agent, and 1 part of anti-PID additive were prepared. The melt index of the POE resin was 5 g / 10 min. The anti-aging additive included 0.03 parts of ultraviolet light absorber and 0.01 parts of light stabilizer. The ultraviolet light absorber was 2-(2'-hydroxy-5'-octylphenyl)-benzotriazole, and the light stabilizer was bis(2,2,6,6,-tetramethyl-4-piperidinyl) sebacate. The coupling agent was vinyltriperoxide tert-butylsilane, the crosslinking agent was di-tert-butyl peroxide, and the anti-PID additive was polyether block amide copolymer 2. The materials were then mixed according to the proportions and mixed in a mixer at 250 rpm for 2 hours. After the additives were completely absorbed, the film was prepared by casting extrusion molding according to the same method as in Example 1, and then a double-glass photovoltaic module was obtained.

[0045] Example 3 (Polyether block amide copolymer 3):

[0046] A highly PID-resistant encapsulating film comprises the following raw materials in parts by weight: 90 parts POE resin, 0.2 parts anti-aging agent, 0.1 parts coupling agent, 0.5 parts crosslinking agent, and 3 parts anti-PID agent. The POE resin has a melt index of 14 g / 10 min. The anti-aging agent includes 0.1 parts ultraviolet absorber and 0.1 parts light stabilizer. The ultraviolet absorber is bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, and the light stabilizer is 2-(2H-benzotriazol-2-yl)-6-dodecyl-4-methylphenol. The coupling agent is 3-glycidylpropyltrimethoxysilane. The crosslinking agent is tert-butyl peracetate. The anti-PID agent is polyether block amide copolymer 3. The materials were then proportioned and mixed in a mixer at 250 rpm for 2 hours. After the additives were fully absorbed, the film was prepared by casting and extrusion molding in the same way as in Example 1, and then a double-glass photovoltaic module was obtained.

[0047] Comparative Example 1 (without PID additive):

[0048] This comparative example provides a POE photovoltaic film prepared without anti-PID additives, comprising the following raw materials in parts by weight: 90 parts POE resin, 0.04 parts anti-aging additives, 0.02 parts coupling agent, and 0.3 parts crosslinking agent. The POE resin has a melt index of 5 g / 10 min. The anti-aging additives include 0.03 parts UV absorber and 0.01 parts light stabilizer; the UV absorber is 2-(2'-hydroxy-5'-octylphenyl)-benzotriazole, and the light stabilizer is bis(2,2,6,6,-tetramethyl-4-piperidinyl) sebacate. The coupling agent is vinyltriperoxide tert-butylsilane. The crosslinking agent is di-tert-butyl peroxide. The materials are then proportioned and mixed in a mixer at 250 rpm for 2 hours. After the additives are fully absorbed, the film is prepared by casting and extrusion molding using the same method as in Example 1, and subsequently, a double-glass photovoltaic module is obtained.

[0049] Comparative Example 2 (Polyether ester amide 1):

[0050] This comparative example provides a POE photovoltaic film prepared using polyether ester amide as an anti-PID additive.

[0051] The raw materials include the following parts by weight: 90 parts POE resin, 0.04 parts anti-aging agent, 0.02 parts coupling agent, 0.3 parts crosslinking agent, and 1 part anti-PID agent. The POE resin has a melt index of 5 g / 10 min. The anti-aging agent includes 0.03 parts UV absorber and 0.01 parts light stabilizer. The UV absorber is 2-(2'-hydroxy-5'-octylphenyl)-benzotriazole, and the light stabilizer is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate. The coupling agent is vinyltriperoxide tert-butylsilane. The crosslinking agent is di-tert-butyl peroxide. Specifically, the anti-PID agent is polyether ester amide 1, which has an aromatic ring structure in its molecular chain. The materials are then proportioned and mixed in a mixer at 250 rpm for 2 hours. After the additives are fully absorbed, the photovoltaic film is prepared by casting extrusion molding using the same method as in Example 1.

[0052] Comparative Example 3 (Polyether Block Amide 4):

[0053] This comparative example provides a method for preparing POE photovoltaic films by adding a polyether block amide copolymer with an excessively high soft segment content as an anti-PID additive.

[0054] Including the raw material composition by weight:

[0055] The mixture consisted of 90 parts POE resin, 0.04 parts anti-aging agent, 0.02 parts coupling agent, 0.3 parts crosslinking agent, and 1 part anti-PID agent. The POE resin had a melt index of 5 g / 10 min. The anti-aging agent comprised 0.03 parts UV absorber and 0.01 parts light stabilizer; the UV absorber was 2-(2'-hydroxy-5'-octylphenyl)-benzotriazole, and the light stabilizer was bis(2,2,6,6,-tetramethyl-4-piperidinyl) sebacate. The coupling agent was vinyltriperoxide tert-butylsilane. The crosslinking agent was di-tert-butyl peroxide. The anti-PID agent was polyether block amide copolymer 4. The materials were then proportioned and mixed in a mixer at 250 rpm for 2 hours. After complete absorption of the agents, the encapsulating film was prepared by casting extrusion molding, following the same method as in Example 1.

[0056] Light transmittance test:

[0057] The encapsulating films prepared in Examples 1, 2, 3 and Comparative Examples 1, 2, 3 were left to stand naturally at room temperature for 30 days, and their transmittance was tested. The results are shown in the table below.

[0058] Test results of transmittance of anti-PID encapsulation film

[0059]

[0060] The results show that polyether block amide copolymer (PEBA), as an anti-PID additive, maintains good light transmittance in the photovoltaic film when added to it. However, as an anti-PID additive, polyether ester amide (PEBA), as shown in Comparative Example 2, causes the film to become less resistant to light aging due to the presence of numerous benzene rings in its molecular structure, resulting in a darker color and decreased light transmittance.

[0061] PID test:

[0062] The double-glass photovoltaic modules prepared in Examples 1, 2, and 3 and Comparative Examples 1, 2, and 3 were subjected to PID testing under the same conditions, namely 96h-85℃ / 85RH / -1500V. The test results are as follows:

[0063] Table 1. PID Resistance Performance Test of Double-Glass Photovoltaic Modules

[0064]

[0065] The results show that polyether block amide copolymer, as an additive in photovoltaic encapsulation films, has a significant effect on the anti-PID effect of modules. After 96 hours of aging, the power degradation resistance of double-glass modules changed significantly. Compared with no additive (Comparative Example 2), the power degradation on the front side of Example 2 decreased from 3.69% to 0.17%, and on the back side from 12.74% to 0.24%. Meanwhile, the power degradation behavior of modules in Examples 1, 2, and 3, and Comparative Example 3 (polyether block amide copolymer as an anti-PID additive) was better than that of Comparative Example 2 (polyether ester amide as an anti-PID additive). This is because although the hygroscopic effect of the polyether soft segments plays a role in anti-PID, the presence of the aromatic ring conjugated structure in the polyether ester amide does not effectively dissipate leakage current, thus deteriorating the anti-PID performance of the module.

[0066] UV aging resistance test:

[0067] The encapsulating films prepared in Examples 1, 2, and 3 and Comparative Examples 1, 2, and 3 were subjected to UV aging resistance tests according to the test method of NB / T10200-2019. The test results are shown in the table below.

[0068]

[0069] The polyether ester amide 1 used in Comparative Example 2 has a similar structure to the polyether block amide copolymer 2 used in Example 2, with identical soft segment molecular weight and content, and hard segment molecular weight. The difference lies in the introduction of aromatic ring structures into the molecular chain of its hard segment. The results show that polyether block amide copolymers 1, 2, 3, and 4, when used as additives in photovoltaic films, exhibit better UV aging resistance than polyether ester amide 1. At 120 kW·h / m 2 After 1000h / 2000h of ultraviolet irradiation, the peel strength values ​​of photovoltaic film / glass and photovoltaic film / backsheet showed only a slight decreasing trend. Conversely, due to the presence of aromatic ring structure, the ultraviolet resistance of polyether ester amide 1 decreased significantly. In particular, after 2000h of irradiation, the yellowing index ΔYI of Comparative Example 2 rose to 3.43, which is very close to the standard requirement of 4.0. Therefore, in actual production applications, aging and cracking will inevitably occur, which will seriously affect the performance and efficiency of the solar cells.

[0070] Water vapor transmission rate test:

[0071] The photovoltaic films prepared in Examples 1, 2, and 3 and Comparative Examples 1, 2, and 3 were prepared in parallel three times, resulting in a total of 6 batches of photovoltaic films. The water vapor transmission performance was tested according to the test method of GB / T 26253—2010, and the test results are shown in the table below.

[0072]

[0073] The results show that the water vapor permeability of the film prepared by Comparative Example 3 is significantly improved. This is mainly because the introduction of a large number of polyether soft segments significantly improves the hydrophilicity of the film, thereby enhancing the moisture permeability and reducing the water vapor barrier. The intrusion of water vapor will reduce the lifespan of the photovoltaic module and greatly reduce its performance. This effect is particularly fatal to Topcon cells. Therefore, it does not have any advantages in practical use.

Claims

1. A high-PID-resistant encapsulating film, characterized in that, The ingredients include the following parts by weight: 85-100 parts of base resin, Anti-aging additive 0.01-0.5 parts, Coupling agent 0.05-1 part, Crosslinking agent 0.1 to 1 part, 1-5 parts of anti-PID additive; The anti-PID additive is a polyether block amide copolymer (PEBA) containing aliphatic polyamide hard segments and flexible polyether soft segments, wherein the polyether block amide copolymer contains 35-65% polyether segments by weight and 35-65% aliphatic polyamide segments by weight. In the polyether block amide copolymer, the polyether soft segment is a polyethylene glycol segment, a polypropylene glycol segment, or a polybutane glycol segment, and the aliphatic polyamide segment is a polyamide segment prepared by reacting an aliphatic diamine with an aliphatic diacid. The aliphatic diamine is a C6-C20 alkyl diamine, and the aliphatic diacid is a C6-C20 alkyl diacid; The number-average molecular weight of the polyether segments is 500-4500 g / mol, and the number-average molecular weight of the aliphatic polyamide segments is 500-3000 g / mol. The base resin is one or both of POE resin or EVA resin.

2. The encapsulating film according to claim 1, characterized in that, The melt index of EVA resin is 15-30 g / 10 min, and the VA content is 28-33%; the melt index of POE resin is 2-50 g / 10 min.

3. The encapsulating film according to claim 1, characterized in that, The anti-aging additives include one or more of ultraviolet light absorbers and light stabilizers; The ultraviolet absorber is selected from one or more of 2,4-dihydroxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, 2-(2'-hydroxy-5'-octylphenyl)-benzotriazole, 2-[2,4-bis(2,4-dimethylyl)-2-(1,3,5-triazinyl)5-octyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-hexyloxyphenol, bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate or 2,2,6,6-tetramethyl-4-piperidinyl stearate; The light stabilizer is selected from one or more of 2-(2H-benzotriazol-2-yl)-6-dodecyl-4-methylphenol, bis(2,2,6,6,-tetramethyl-4-piperidinyl) sebacate or polysuccinate (4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol).

4. The encapsulating film according to claim 1, characterized in that, The coupling agent is a silane coupling agent selected from one or more of the following: methacryloyloxypropyltrimethoxysilane, 3-methacryloyloxypropylmethyldimethoxysilane, vinyltriethoxysilane, vinyltriperoxytert-butylsilane, γ-methacryloyloxypropyltrimethoxysilane, vinyltriacetoxysilane, 3-glycidylpropyltrimethoxysilane, 3-aminopropyltriethoxysilane, or vinylalkoxysilane oligomers.

5. The encapsulating film according to claim 1, characterized in that, The crosslinking agent is selected from one or more of the following: di(4-methylbenzoyl)peroxide, cumene peroxide, di-tert-butyl peroxide, dicumene hydrogen peroxide, 2,5-dimethyl-2,5-di-tert-butyl peroxide, tert-butyl peroxyhexyl carbonate, benzoyl peroxide, cyclohexanone peroxide, tert-butyl peroxybenzoate, tert-butyl peracetate, tert-butyl peroxide-3,5,5-trimethylhexanoate, trimethylolpropane trimethacrylate, 2-trimethylolpropane tetraacrylate, pentaerythritol triacrylate, propoxylated neopentyl glycol diacrylate, diethylene glycol dimethacrylate, or ethoxylated trimethylolpropane triacrylate.

6. A method for preparing an encapsulating film according to any one of claims 1-5, characterized in that, The base resin, anti-aging additive, coupling agent, crosslinking agent, and anti-PID additive are mixed evenly and stirred. After the additives are fully absorbed, the mixture is extruded and molded at a temperature of 70-120℃ to obtain a high anti-PID encapsulation film for photovoltaic modules.

7. The preparation method according to claim 6, characterized in that, The processing method is either casting or calendering.

8. The preparation method according to claim 7, characterized in that, The raw materials are mixed and stirred at high speed at 90-300 rpm for 2-5 hours.

Citation Information

Patent Citations

  • Copolymers comprising polyamide blocks and polyether blocks and having improved mechanical properties

    CN101426834A

  • Composition for forming anti-PID packaging adhesive film, anti-PID packaging adhesive film and solar module

    CN112898920A

  • Packaging adhesive film with high PID resistance and preparation method thereof

    CN113122164A

  • High-PID-resistance composite packaging adhesive film and preparation method thereof

    CN113234402A

  • Anti-PID (potential induced degradation) packaging adhesive film and preparation method thereof

    CN106221592A